(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Recurrent liver echinococcosis remains one of the most difficult problems in abdominal surgery in endemic regions. Re-identification of echinococcal cysts after a previously performed operation may be associated with different mechanisms: residual lesion, implantation relapse, or true re-invasion. However, in clinical practice, these variants are often combined under the general term "recurrent", which makes it difficult to objectively assess the quality of initial treatment, choose a repeat surgical approach, and determine preventive priorities. In this regard, it is an urgent task to develop a tool that allows for the differentiation of repeated forms of liver echinococcosis based on available clinical and anatomical criteria.